Studies on the resting behaviour and host choice of Anopheles gambiae and An. arabiensis from Muleba, Tanzania. Issue 3 (26th February 2018) - Charlwood, J. D.; Kessy, E.; Yohannes, K.; Protopopoff, N.; Rowland, M.; LeClair, C.
Abstract: The relative efficacy of a mechanical (Prokopack) collection method vs. manual aspiration in the collection of resting mosquitoes was evaluated in northern Tanzania before and after an intervention using indoor residual spraying and longlasting insecticide‐treated nets. In smoke‐free houses mosquitoes were collected from the roof and walls, but in smoky houses mosquitoes were found predominantly on the walls. Anopheles gambiae (Diptera: Culicidae) constituted 97.7% of the 312 An. gambiae complex specimens identified before but only 19.3% of the 183 identified after the intervention. A single sampling with the Prokopack collected a third of the available insects. Anopheles gambiae completed its gonotrophic development indoors, whereas Anopheles arabiensis did so outdoors. In both species gonotrophic development took 2 days. Most unfed resting An. arabiensis collected outdoors were virgins, whereas the majority of engorged insects were parous (with well‐contracted sacs). Daily survival was estimated to be 80.0%. Only 9.4% of the engorged An. arabiensis collected outdoors and 47.1% of those collected indoors had fed on humans. Using the Prokopack sampler is more efficient than manual methods for the collection of resting mosquitoes. Malaria transmission may have been affected by a change in vector composition resulting from a change in feeding, rather than reduced survival. Monitoring the proportions of members of the An. gambiae complex may provide signals of an impending breakdown in control. Abstract : Following an intervention with longlasting insecticide‐treated nets and indoor residual spraying, the endophilic, anthropophagic mosquito Anopheles gambiae was replaced by its exophilic and zoophagic sibling species Anopheles arabiensis . The majority of unfed mosquitoes collected resting were newly emerged, whereas the majority of engorged insects were parous. Collecting with the Prokopack mechanical aspirator was more efficient than manual collecting for the sampling of resting mosquitoes inside houses.